Implementasi Kebijakan Penegakan Hukum Terhadap Warga Negara Asing yang Melanggar Peraturan Keimigrasian di Kantor Imigrasi TPI 1 Pekanbaru - Reza Patrisia Putri; Mahmuzar (Al-Manar Journal of Public Administration and Management, 2025)
This study aims to understand the implementation of law enforcement policies against foreign nationals (WNA) who violate immigration regulations and to identify the factors hindering this implementation at the Class I Immigration Office, Immigration Checkpoint (TPI) Pekanbaru. Using a qualitative approach with a phenomenological study to capture the experiences of policy implementers and relevant parties, data were obtained through in-depth interviews with relevant informants. The findings indicate that the implementation faces significant obstacles categorized based on Edward III's theory: communication, resources, implementer attitudes, and bureaucratic structure. Communication barriers include language difficulties between immigration officers and foreign nationals and a lack of socialization to the public. In terms of resources, although there is a sufficient number of personnel, the lack of responsiveness of some officers and uneven technological facilities slow down the law enforcement process. The attitudes of policy implementers, who are sometimes unfriendly and overly rigid, affect the comfort and trust of foreign nationals. Additionally, the hierarchical bureaucratic structure delays decision-making, especially in handling immigration violations. To improve the effectiveness of policy implementation, reforms in communication through multilingual services, equal distribution of technological facilities, training for policy implementers to enhance professionalism, and simplification of the bureaucratic structure are needed. These measures are expected to expedite the handling of violations and support more optimal law enforcement against foreign nationals in Indonesia.